The benefits of being moral - Tan, Dion Shi Han (Nanyang Technological University, 2021)
Morality is generally perceived as being beneficial for the agent carrying out the moral acts. This is because accounts of right action are explained, to a certain extent, by facts about welfare. To do good is to either bring about a state of affairs that benefits a large number of people or to have a mindset grounded in beneficence when we interact with others. However, many theories of welfare also are explained by facts relating to moral rightness in that acting morally directly benefits a person. This leads to a situation where morality is partially explained by welfare which is partially explained by morality, creating a structural circularity and highlight an explanatory inadequacy in our current approach towards ethics and welfare. This paper advances that the solution to this circularity problem is to reject that welfare should be morality-involving whereby theories of welfare should not include moral virtue as an intrinsic good to human wellbeing. I argue that this view is superior to the solutions of accepting that the circularity is not problematic, rejecting that morality should be welfare-involving and William Lauinger’s two-different-senses-of- “morality” approach.